PENYULUHAN GIZI SEIMBANG ISI PIRINGKU UNTUK MENCEGAH KURANG ENERGI KRONIK PADA IBU HAMIL DI PUSTU WALI - Jayanthi Petronela Janggu; Eufrasia P Padeng; , Putriatri K Senudin; Agnesia Parus (Bajang Institute, 2021)
Fulfillment of balanced nutrition in pregnant women is an effort to improve maternal health during pregnancy. By getting a balanced nutritional intake can reduce health risks to the fetus and mother. Therefore, it is necessary to have sufficient knowledge of nutrition in pregnant women so as to prevent the risk of pregnancy which can lead to illness and death. Balanced nutrition of the contents of my plate for pregnant women is one of the guidelines for healthy food that meets the composition of the contents of my plate so that nutritional needs are fulfilled. The purpose of this service is to increase knowledge about the balanced nutrition of the contents of my plate for pregnant women. The target of this service activity is pregnant women at Pustu Wali, Manggarai Regency, East Nusa Tenggara. The method used is counseling or lectures, discussions and pretest and posttest to find out the description of knowledge from pregnant women. The results of this service indicate that there is a difference in knowledge after counseling, namely an increase in knowledge on the average value of 6.13 to 8.80.